Effect of VAM fungi on nutrient uptake and plant growth performance of soybean - and M.K. BHATNAGAR, B.L. MALI, RAKESH SHAH (Indian Phytopathology, 2009)
Inoculation of Glomus fasciculatum and G. mosseae at the time of sowing was found essential for maximum plant growth, root colonization and spores production. VAM application at 10, 20 and 30 days after sowing had progressively reduced their beneficial effect. Mycorrhizal inoculation by layering method is highly significant while the effectively decreased with delayed application of inoculum at different time interval. This may be due to possible contact of VAM fungi with roots of soybean plants at initial stage eventually resulting in good colonization and establishment. Both VAM fungi were found most effective at higher concentration (40 and 50 g / pot) where maximum plant growth, colonization, spores production and nutrient (NPK) uptake was recorded. The effectively was low at lower (10 g/pot) VAM concentration tried. The response, however was much better in sterilized compared to unsterilized soil. Percent content and uptake of nutrient (NPK) was higher in soybean plants inoculated with VAM fungi. The increase in the nutrient uptake of NPK was found best when VAM inoculum applied at the time of sowing. The nutrient uptake increased with the increased in VAM inoculum concentration. The best NPK content and uptake were observed at 40 and 50 g inoculum per pot which shown good VAM colonization with improved uptake of nutrient by the soybean roots in rhizosphere area.